The terror enigma 9/11 and the Israeli connection - Raimondo, Justin (IUniverse, 2003)
With information culled from mainstream sources, author Justin Raimondo shows in this eye-opening book that Israel's spies in the United States had been watching the 9/11 terrorists. As the terrorists were planning the biggest and deadliest terrorist attack in American history, Israeli agents in the U.S. were watching them 24/7-living literally "next door to Mohammed Atta," according to one account. Did Israeli intelligence have foreknowledge of 9/11? As one law enforcement source close to the investigation told Fox News, the real question is: how could they not have known? But if they knew, then why didn't they tell us?